High-level ePVS was accompanied by an increase in kidney transplant failure risk: analysis based on the MIMIC-IV database - Zhou, Zhirong; Zhang, Lin; Zhang, Delin; Yang, Yan; Ou, Shuiping (Frontiers in Immunology, 2025)
BackgroundThe prognosis of kidney transplantation is currently assessed primarily through clinical monitoring, which involves considerable time and financial costs. Estimated plasma volume status (ePVS) has emerged as a straightforward and efficient method for evaluating patient condition. However, the potential prognostic significance of ePVS in kidney transplant recipients has yet to be thoroughly investigated.MethodsThe clinical data for the patient were obtained from the MIMIC-IV database. ePVS was calculated based on hematocrit and hemoglobin values upon admission. Baseline characteristics were compared according to ePVS quartiles, and the relationship between ePVS levels and kidney transplant failure (KTF) in patients was assessed using a Logistic regression model.Results4,421 eligible subjects (2,584 males and 1,837 females) with an average age of 52.53 ± 13.00 years old were included in our study. 3,661 (82.80%) had no kidney transplant failure (No-KTF) and 760 (17.20%) had kidney transplant failure (KTF). The ePVS values exhibited a skewed distribution, with the admission patients concentrated in the range of 4–8 mL/g and the discharge patients concentrated in the range of 6–10 mL/g. The ePVS level in the KTF group (7.20 [5.78, 8.85]) was significantly higher than that in the non-KTF group (6.12 [4.95, 7.60]) (p< 0.001) at admission. The ePVS level in the KTF group (8.18 [6.71, 9.47]) was significantly higher than that in the non-KTF group (7.01 [5.56, 8.55]) (p< 0.001) at discharge. The sensitivity values were 0.851 and 0.805, the specificity values were 0.744 and 0.81, and the AUC values were 0.861 and 0.847, respectively, at admission and discharge. In our subgroup analysis, including interactive validation, we found that regardless of admission or discharge, the risk of KTF was greater when ePVS increased in Non-heart failure (HF) (P-interaction<0.001).ConclusionIn this study, we found that higher ePVS values were accompanied by an increase in KTF risk, and this association proved robust and independent of age, gender, and comorbidities. Additionally, in our subgroup analysis, including interactive validation, we found that regardless of admission or discharge, the risk of KTF was greater when ePVS increased in non-heart failure. Therefore, ePVS may be an important reference parameter for kidney transplant patients and help improve risk stratification.